Taxonomic revision of the New World genus Chlorotabanus Lutz, 1913 (Diptera: Tabanidae) - Krolow, Tiago Kütter; Henriques, Augusto Loureiro (Zootaxa, 2010)
The genus Chlorotabanus Lutz is revised herein based on examination of external morphology of type material and specimens from Brazilian and international institutions (total of 2,134 specimens, 201 males and 1,933 females). Eight currently valid species are recognized: C. crepuscularis (Bequaert, 1926); C. fairchildi Wilkerson, 1979; C. flagellatus Krolow & Henriques, 2009; C. inanis (Fabricius, 1787); C. leucochlorus Fairchild, 1961; C. mexicanus (Linnaeus, 1758); C. ochreus Philip & Fairchild, 1956; C. parviceps (Kröber, 1934). Three new species are described: C. falsiflagellatus n. sp. (Brazil, Amazonas), C. leuconotus n. sp. (Amazon region) and C. microceratus n. sp. (Brasil, Maranhão). Tabanus tetrapunctus Thunberg, 1827, previously synonymous with C. mexicanus, here is synonymous with C. crepuscularis (new synonymy). We provide diagnosis, descriptions, redescriptions, distribution records, illustrations and discussion for all species, as well as a dichotomous key for identification of females.